Russian Federation : Financial Sector Assessment Program: Technical Note-Stress Testing. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the results of the stress testing carried out as part of the 2016 Financial Sector Assessment Program for the Russian Federation. The stress tests focused on banks, reflecting the structure of the Russian financial sector, which is relatively small and bank dominated. The results showed that the banking system is likely to need additional capital. Even in the baseline scenario, certain banks will need new capital owing to low profitability and increasing credit losses. The required resources are higher in the stress scenarios, but remain manageable. If public funds are needed for recapitalization, there is sufficient fiscal space, provided that fiscal policy remains prudent.